Approach to the design of sampling procedures for economic surveys in Trinidad & Tobago - Clarke, Christopher Martin (ISER MonaJA, 1993)
Examines the arguments for the use of judgement methods of sampling in the context of economic surveys in Trinidad & Tobago.